Antisemitism in Galicia: agitation, politics, and violence against Jews in the late Habsburg monarchy - Buchen, Tim (Austrian and Habsburg studies, 2020)
ANTISEMITISM IN GALICIA -- Contents -- Illustrations -- Preface to the English Edition -- Introduction -- Chapter 1 - Agitation -- Chapter 2 - Violence -- Chapter 3 - Politics -- Chapter 4 - Summary -- Untitled -- Epilogue -- Bibliography -- Index of Persons -- Index of Places -- Index of Subjects.